Exploring the para-social relationship dynamics of a Bangladeshi Facebook author with the local community - Asadi, Samiya (SIMULACRA: JURNAL SOSIOLOGI, 2025)
Facebook has redefined digital interactions, shaping community formation and identity construction. This study explores how a Bangladeshi Facebook-born author uses social presence strategies to build community attachment, foster parasocial relationships, and enhance digital authorship. By negotiating cultural and social capital, the author uses digital networks for self-promotion and audience engagement. Using a mixed-methods approach, the study applies parasocial relationship and social presence theory to explore three key questions: How does a celebrity maintain digital authorship for promotion and community attachment? What are the different dimensions of social presence between celebrities and audiences? How have parasocial relationships evolved in the digital age? The study analyzed Facebook posts and comments from Mouri's official novel Facebook page for quantitative content analysis and conducted in-depth interviews with the author and her six fans for qualitative insights. Findings show that the author strategically used UGC (user-generated content), among other strategies, to strengthen community ties. Audiences engaged primarily through interactive strategies, followed by affective and cohesive strategies. A nuanced mix of these strategies was also observed. In addition, open communication facilitated both positive and negative self-disclosure, making the parasocial relationship more reciprocal, interactive, and engaging. This study highlights the sociological dynamics of technology, connectivity, and digital authorship.